(Invited) Characteristics of Si Single-Electron Transistor under Illumination. (3rd July 2019) - Takahashi, Yasuo; Sinohara, Michito; Arita, Masashi; Tsurumaki-Fukuchi, Atsushi; Fujiwara, Akira; Ono, Yukinori; Nishiguchi, Katsuhiko; Inokawa, Hiroshi
Abstract : Photo-excited carriers in Si quantum islands and their surrounded area exhibit interesting features due to electron-hole generation. We show Si single- hole transistor (SHT) characteristics in a Si single-electron transistor (SET) comprising n-type source and drain electrodes under illumination. Holes excited in the Si are expected to flow through the SET island by applying negative gate voltages. Interesting phenomenon is the co-existence of electrons and holes around the island. In a SET, when holes generated by photo-excitation are trapped in the one side (either top or bottom side) of the SET island under the vertical electric field, the SET characteristics are changed depending on the number of trapped holes because effective total number of electrons can be negative. Here, we show the characteristics of photo-excited SETs without strong vertical electric fields.